Wind Energy at Nygårdsfjellet – Norway. Wind field characterization and modelling - Bilal, Muhammad (UiT Norges arktiske universitet, 2016)
The papers I and II of this thesis are not available in Munin. Paper I: Bilal, M., Birkelund, Y., Homola, M.: "High winds at Nygårdsfjell”. Available in Journal of Clean Energy Technologies 2015, 3(2):106-109. Paper II: Bilal, M., Araya, G., Birkelund, Y., Sridhar, N., Parameswaran, S.: "Wind Flow Over a Complex Terrain in Nygårdsfjell, Norway". Available in ASME proceedings 2015, paper ES2015-49188, pp. V002T19A005. The research focuses on the characterization of wind flow over complex terrain of Nygårdsfjell and numerical wind flow modelling. In the context to research focus, the main contributions of this research thesis are within the following areas: Characterization of wind flow at the Nygårdsfjell wind farm, situated in the arctic circle in Norway. Wind data is collected from the anemometers installed on the wind turbines and thereafter analysed for understanding the existing wind patterns. The analysis established existence of bi-directional high winds at Nygårdsfjell wind farm particularly during colder periods. Computational fluid dynamic (CFD) solver FLUENT is used to model the wind fields over the complex terrain of Nygårdsfjell. Overall, the shear stress transport model gives good simulation results that explains the speed up effects at the turbine location, which makes the wind farm a suitable site for wind energy. Local terrain effects on the wind flow over Nygårdsfjell are modelled by coupling meso-micro scale models. One set of meso-scale winds are generated from Weather Research and Forecasting model, whereas the other set is taken from the Modern-Era Retrospective Analysis for Research and Applications dataset. CFD based numerical solver, WindSim, is used as micro-scale coupling partner. The proposed coupled model achieved improvements in wind speed modelling. A basic method for preliminary wind resource assessment at remote sites is proposed. The method is a combination of interpolation and extrapolation of wind data from the surrounding sites to the potential wind farm site. However, due ...